2017
DOI: 10.3382/ps/pex264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low incubation temperature and low ambient temperature until 21 days of age on performance and body temperature in fast-growing chickens

Abstract: Thermal manipulation during embryogenesis was previously reported to decrease the occurrence of ascites and to potentially improve cold tolerance of broilers. The objective of our study was to explore the effects of the interaction of cold incubation temperatures and cool ambient temperatures until 21 d of age on performance and body temperature. Ross 308 eggs were incubated either under control conditions I0 (37.6°C) or with cyclic cold stimulations I1 (6 h/d at 36.6°C from d 10 to 18 of incubation) or with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
4
7
1
Order By: Relevance
“…Incubation parameters such as temperature [2], light [3] or noise [4] are known to impact development and behavior. In a context of climate change, with an increase of global average temperature and the occurrence of extreme heatwaves [5], numerous studies have reported the utilization of the thermal-manipulation (TM) of eggs during the incubation period to improve the later-life heat tolerance of chickens [2,[6][7][8][9][10][11][12][13][14][15][16] and turkeys [17,18] or to modify muscle development in ducks [19][20][21]. The TM consists in a modification of the incubation temperature of avian eggs during embryogenesis, which is often cyclic and applied during defined periods of the embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Incubation parameters such as temperature [2], light [3] or noise [4] are known to impact development and behavior. In a context of climate change, with an increase of global average temperature and the occurrence of extreme heatwaves [5], numerous studies have reported the utilization of the thermal-manipulation (TM) of eggs during the incubation period to improve the later-life heat tolerance of chickens [2,[6][7][8][9][10][11][12][13][14][15][16] and turkeys [17,18] or to modify muscle development in ducks [19][20][21]. The TM consists in a modification of the incubation temperature of avian eggs during embryogenesis, which is often cyclic and applied during defined periods of the embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning hatching parameters, on the one hand, negative effect of incubation temperature I 0 or I 1 was observed neither on hatchability (more than 95% in both conditions) or on body temperature nor on BW of hatched chicks, as previously shown by Shinder et al. (2011) and Nyuiadzi et al. (2017) .…”
Section: Discussionmentioning
confidence: 45%
“…The parameters considered consequently to these treatments relate to growth performance and feed efficiency, but also meat processing quality and defects, and animal welfare criteria. Previous experiments had permitted to compare the effects of 2 published methods of cold embryo manipulation ( Shinder et al., 2011 , Yalçin et al., 2012 ) combined to continuous or fluctuating 4°C colder or standard postnatal temperatures ( Nyuiadzi et al., 2017 ) during the first 21 d of age in Ross 308 broilers. These studies, conducted in pens for the first two and in cages for the latter, allowed determining thermal conditions of incubation and postnatal rearing enhancing cold adaptation of chicks that had little to no impact on performance in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations